2018
DOI: 10.1037/pro0000194
|View full text |Cite
|
Sign up to set email alerts
|

Best practices of mobile health in clinical care: The development and evaluation of a competency-based provider training program.

Abstract: This article describes the development and evaluation of a training program for behavioral health providers on the integration of mobile health applications (health apps) in clinical care. The purpose was to train military and Department of Veterans Affairs (VA) providers in the use and current research of various behavioral health apps. The training focused on 5 core competencies: gaining knowledge on the evidence base for using mobile apps in behavioral health practice, effective integration of mobile techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…In the past decade alone, the use and availability of telehealth (i.e., technology‐based delivery of general healthcare) resources have increased exponentially (Armstrong et al, 2018). A study of a nationally representative consumer survey found that for mental and physical health services, live video communication rates rose from 6.6% to 21.6% between 2013 and 2016 (Park et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the past decade alone, the use and availability of telehealth (i.e., technology‐based delivery of general healthcare) resources have increased exponentially (Armstrong et al, 2018). A study of a nationally representative consumer survey found that for mental and physical health services, live video communication rates rose from 6.6% to 21.6% between 2013 and 2016 (Park et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Virtual care health technologies such as synchronous and asynchronous telehealth, mobile applications, text-messaging applications, wearable/implantable biosensors, and patient-generated health data deployed in the setting of an integrated electronic health record (EHR) with and advanced analytic capabilities create the potential for huge benefits in the delivery and coordination of clinical care (Brown et al, 2014 ; Hermes et al, 2019 ; Hilty et al, 2019 ; Keyworth et al, 2018 ; Rathbone & Prescott, 2017 ). Barriers to implementation of virtual care include systemic barriers at the organizational level (governance models, lack of guidance regarding clinical integration), environmental (low levels of digital health literacy, lack of understanding of benefits, lack of training, learning new workflows), lack of infrastructure (poor wi-fi, lack of logistics for supplying equipment and access, poor integration of EHR systems), logistical barriers (scheduling, staffing), lack of resources (space, equipment, funding, time), challenges with collaboration (bureaucratic delays, communication), and policy issues (Armstrong et al, 2018 ; Hilty et al, 2018 ; Maheu et al, 2018 ; Muir et al, 2020 ; Torous et al, 2018 ; Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apps were used as examples for direct hands-on practice during a seven-hour training. The findings collected from training participants indicate that knowledge about mobile health applications had improved three months after the training, with 92% of trainees using apps for patient care (Armstrong et al, 2018). However, the study did not assess the overall impact on patient outcomes, but it is suggested that apps could empower patients to be more involved in their care.…”
Section: Telehealthmentioning
confidence: 97%
“…Clinical supervision is encouraged to help maintain clear boundaries, but since mHealth is asynchronous, on-call supervision may be necessary during training (Hilty et al, 2020). Armstrong et al (2018) describe the development and evaluation of a competency-based training program centered on the integration of mHealth into the military and Veterans Affairs (VA) behavioral health settings. A curriculum focused on DoD/VA developed mobile apps was created; however, the curriculum could be of use with any mHealth app.…”
Section: Telehealthmentioning
confidence: 99%
See 1 more Smart Citation